مساهمة التقييم المالي للأوراق المالية في اتخاذ القرارات الاستثمارية - رميصاء, بن عثمان; سمية, دودي; كريمة, دباخ (University of eloued جامعة الوادي, 2020)
"تهدف هذه الدراسة الى مدى تأثير تقييم الأوراق المالية ومساهمتها على اتخاذ القرار الاستثماري ومعرفة كيف يتم تطبيق هذا التقييم على الأوراق ق المالية في الواقع العملي واهم الصعوبات التي تحد من فعاليته وتنعكس سلبا على اتخاذ القرار الاستثماري بشكل سليم، اضافة الى معرفة كيف تتم المفاضلة بين هذه المؤسسات وعلى هذا الأساس زمن أجل معالجة اشكالية الدراسة واختبار فرضياته تم تكوين عينة متكونة من مؤسسة استثمارية المدرجة في بورصة عربية "" قطر"" خلال الفترة ممتدة من (2009-2019) وهذا باتباع المنهج الاستكشافي واستعانة ببرنامج spss22ثم معالجة معطيات المتحصل عليها التي تخص مؤسسة ""ميرة"" المدروسة خلال نفس الفترة. وقد خلصت الدراسة إلى أن التقييم الأوراق المالية يساعد المستثمرين بشكل كبير على اتخاذ القرار الاستثماري بخصوص مؤسساتهم، وهذا في حالة الاستعانة بمجموعة من الطرق والاساليب العملية المتكاملة فيما بينها، كذلك بنيت الدراسة أن القرار الاستثماري المتخذ من قبل مثل هذه المؤسسات محل الدراسة يبن فقط على معايير التقييم التي تتم بحالة اليقين، و يرجع هذا لعدم توفر المعلومات الازمة لتطبيق المعايير الأخرى، وبالتالي فقرارهم يكون غير سليم بشكل كبير. "" This study aims to the extent of the impact of securities evaluation and is contribution to investment decision-making and knowing how this evaluation is applied to securities in practice and the most important difficulties that limit its effectiveness and reflect negatively on investment decision- making in a proper way, in addition to knowing how the comparison Among these institutions On this basis, in order to address the problem of the study and test its hypotheses, a sample consisting of an investment institution listed on the Arab Stock Exchange ""Qatar"" was formed during the period from(2011-2019)and this is by following the exploratory approach and using a programspss22Then, the data obtained by the approved person belonging to the Meera Foundation studied during the same period. the evaluation of securities greatly helps that The study concluded the investors in making the investment decision regarding their institutions ;and this is in the case of using a set of integrated methods and practical methods among them The study built that the decision taken by such institutions under study shows only On the evaluation criteria that are carried out with certainty, this is due to the lack of information necessary to implement other criteria, and therefore their decision largely incorrect. "
مذكرة ماستر تدقيق محاسبي
Keywords: تقييم الأوراق المالية، اتخاذ القرار الاستثماري، طرق التقييم.; stock appraisal, investment decision making, devaluation methods